2013
DOI: 10.1103/physrevb.87.064406
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetism in EuNiGe3

Abstract: The synthesis and crystallographic and physical properties of polycrystalline EuNiGe3 are reported. EuNiGe3 crystallizes in the noncentrosymmetric body-centered tetragonal BaNiSn3-type structure (space group I4mm), in agreement with previous reports, with the Eu atoms at the corners and body center of the unit cell. The physical property data consistently demonstrate that this is a metallic system in which Eu spins S = 7/2 order antiferromagnetically at a temperature TN = 13.6 K. Magnetic susceptibility χ data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
30
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 20 publications
(15 reference statements)
7
30
1
Order By: Relevance
“…5). The hump in the ordered state is particularly noticeable in compounds containing Eu 2+ or Gd 3+ with S = 7/2, and is not visible for lower S, e.g., S = 1/2 [36,37,38]. The magnetic contribution to the entropy S mag was obtained by integrating the C mag /T versus T .…”
Section: Resultsmentioning
confidence: 99%
“…5). The hump in the ordered state is particularly noticeable in compounds containing Eu 2+ or Gd 3+ with S = 7/2, and is not visible for lower S, e.g., S = 1/2 [36,37,38]. The magnetic contribution to the entropy S mag was obtained by integrating the C mag /T versus T .…”
Section: Resultsmentioning
confidence: 99%
“…EuPtGe 3 was found to order below T N = 11 K with a commensurate equal-moment (EM) antiferromagnetic (AFM) structure with the magnetic moments confined within the basal a-b plane [14]. In subsequent investigations, the magnetic properties of polycrystalline samples of EuPdGe 3 and EuNiGe 3 were determined [15,16]. For both compounds a single AFM phase transition was evidenced to occur at T N = 12.4 K and 13.6 K, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…Nevertheless, based on the obtained data, it was suggested in Ref. [16] that EuNiGe 3 possesses a collinear EM-AFM structure with the europium spins being aligned ferromagnetically in the a-b plane and coupled ferromagnetically along the c-axis. In the most recent study [17], however, made on single crystals of EuNiGe 3 , it was revealed that the EM-AFM arrangement occurs only below T N2 % 10.5 K, with the magnetic moments being almost parallel to the c-axis, while in the intermediate temperatures up to T N1 % 13.2 K, the AFM structure has probably an incommensurate amplitude-modulated (AM) character.…”
Section: Introductionmentioning
confidence: 96%
“…In the rst literature report [10], based on polycrystalline data, the compound was described as a simple A-type collinear antiferromagnet with T N = 13.6 K. However, in the most recent study on single crystals [11] In this contribution, we report on the low-temperature physical behaviours in the two novel representatives of the EuTGe 3 series, namely EuCoGe 3 and EuRhGe 3 .…”
Section: Introductionmentioning
confidence: 99%